Production of 3-Hydroxypropanoic Acid From Glycerol by Metabolically Engineered Bacteria - Jers, Carsten; Kalantari, Aida; Garg, Abhroop; Mijakovic, Ivan (Frontiers in Bioengineering and Biotechnology, 2019)
3-hydroxypropanoic acid (3-HP) is a valuable platform chemical with a high demand in the global market. 3-HP can be produced from various renewable resources. It is used as a precursor in industrial production of a number of chemicals, such as acrylic acid and its many derivatives. In its polymerized form, 3-HP can be used in bioplastic production. Several microbes naturally possess the biosynthetic pathways for production of 3-HP, and a number of these pathways have been introduced in some widely used cell factories, such as Escherichia coli and Saccharomyces cerevisiae. Latest advances in the field of metabolic engineering and synthetic biology have led to more efficient methods for bio-production of 3-HP. These include new approaches for introducing heterologous pathways, precise control of gene expression, rational enzyme engineering, redirecting the carbon flux based on in silico predictions using genome scale metabolic models, as well as optimizing fermentation conditions. Despite the fact that the production of 3-HP has been extensively explored in established industrially relevant cell factories, the current production processes have not yet reached the levels required for industrial exploitation. In this review, we explore the state of the art in 3-HP bio-production, comparing the yields and titers achieved in different microbial cell factories and we discuss possible methodologies that could make the final step towards industrially relevant cell factories.